ANALISA KONFLIK KELUARGA-PEKERJAAN DAN STRES KERJA TERHADAP KOMITMEN ORGANISASI PADA PEGAWAI WANITA DI BKBPP KOTA KENDARI - Zulfitri Jamal (Jurnal Riset Bisnis Indonesia, 2014)
The objectives of this study are to find out the influence of Work Interfering With The Family (WIF),Family Interfering With The Work (FIW) and work stress on Organization Commitment. This researchis an explanatory study with 42 sampels analyzed by descriptive and path analysis to find out therelationship among the variables. The result of this study are: 1)Work Interfering With The Family(WIF) significantly influences the work stress, 2) Family Interfering With The Work (FIW) significantlyinfluences the work stress, 3) Work Interfering With The Family (WIF) significantly influences theOrganization Commitmen, 4) Family Interfering With The Work (FIW) significantly influences theOrganization Commitmen, 5) Work stress significantly influences the Organization Commitmen.Keywords: Work Interfering With The Family (WIF), Family Interfering With The Work (FIW), workstress, Organization Commitment.